The pyramid principle - Minto, Barbara (Financial Times Prentice Hall, 2021)
This book reveals that the mind automatically sorts information into distinctive pyramidal groupings. However, if any group of ideas are arranged into a pyramid structure in the first place, not only will it save valuable time and effort to write, it will take even less effort to read and comprehend it
Auf dem Umschlag: Logic in writing und thinking
Keywords: Führungskraft; Logisches Denken; Sachtext; Textproduktion; Formulierung; Denktraining; Business communication; Business writing; English language / Business English